Differed IL-1 Beta Response between Active TB and LTBI Cases by Ex Vivo Stimulation of Human Monocyte-Derived Macrophage with TB-Specific Antigen. (29th October 2019) - Lee, Meng-Rui; Chang, Lih-Yu; Chang, Chia-Hao; Yan, Bo-Shiun; Wang, Jann-Yuan; Lin, Wan-Hsin
Abstract : Background . The difference of macrophage-specific interleukin-1 beta (IL-1b) response between latent tuberculosis infection (LTBI) and active tuberculosis (TB) remains less studied. Method . We performed this prospective study and recruited active TB patients, contacts with LTBI, and uninfected contacts. The gene and protein expression of human monocyte-derived macrophage (hMDM) after ex vivo stimulation by early secretory antigenic target-6KD (ESAT-6) and tuberculin purified protein derivatives (PPD) was studied by real-time PCR and flow cytometry. The effect of caspase-1 inhibitor was also studied. Result . The IL-1b gene expression after 6 hr ESAT-6 1 μ g/ml stimulation was different among active TB patients (n = 12 ), LTBI cases (n = 12 ), and uninfected contacts (n = 23 ) (log fold change: 0.98 ± 1.26 vs. 2.20 ± 0.96 vs. 2.20 ± 0.96, P = 0.013 ). The IL-1b gene expression at 24 hours was higher than that at 6 hours in LTBI cases (n = 4 ) and uninfected contacts (n = 6 ). After 24 hr ESAT-6 1 μ g/ml stimulation, the percentage of IL-1b-expressed hMDM was borderline lower in the active TB patients (n = 9 ) than in the LTBI cases (n = 10 ) (14.0 ± 11.2 % vs. 31.6 ± 22.5 %, P = 0.065 ). Compared with ESAT-6 1 μ g/ml stimulation but without the addition of caspase-1 inhibitor (CasI) (55.6 ± 16.3 % ), the percentage of IL-1b-positive hMDMs decreased after addition of CasI (50 μ g/ml CasI: 49.8 ± 18.2 %, P = 0.078 ; 100 μ g/ml CasI: 46.6 ± 20.8 %, P = 0.030 ; 150 μ g/ml CasI: 33.7 ± 15.5 %, P = 0.016 ). Conclusions . This study revealed that macrophage-specific IL-1b response differed among different stages of Mycobacterium tuberculosis infection. The role of IL-1b and inflammasome in the process of LTBI progressing to active TB warrants further investigation.